Topical anesthetics most used in pediatric dentistry. Review of the literature - Valdiviezo Dioses, Geraldine Alexia (2022)
Introduction: The pain management during a dental appointment is a challenge that pediatric dentists constantly face, especially during procedures that require the usage of local dental anesthesia. The use of topical anesthesia on oral mucosa can reduce the perception of pain, improving the relationship between the child and the professional. Objective: The objective of the study, was to realize a literature review, about the topical anesthetics most used in pediatric dentistry. Methodology: An information search was count from June 2019 to January 2020 about topical anesthetics used in pediatric dentistry using the platforms: EBSCO, Scielo, Pubmed, Cochrane and Google Scholar, using the key words: dental topical anesthetic, pediatric dentistry, benzocaine. topical, topical lidocaine, EMLA, PLO4%. Results: The initial bibliographic search gave 1733 studies, the information obtained was reviewed considering 19 eligible studies. Conclusions: The most commonly used topical anesthetics in pediatric dentistry according to the literature review were lidocaine and benzocaine. The most used presentations were cream, gel, spray and patches. Its main uses were in oral traumas, before clamping, in extractions of primary teeth with mobility and before infiltration of local anesthesia. No cases of adverse effects were reported in this literature review.